An early warning system for emerging drugs of concern in the emergency department: Protocol for the Western Australian Illicit Substance Evaluation (WISE) study. (14th October 2018) - McCutcheon, David; Raghavan, Mohan; Soderstrom, Jessamine; Oosthuizen, Francois; Douglas, Bianca; MacDonald, Ellen; Fatovich, Daniel
Abstract: Objective: An ever‐increasing number of novel psychoactive substances are being detected worldwide. These emerging drugs have been demonstrated to cause toxicity in clusters, and deaths have been reported. We urgently need to learn more about their effects. We report the protocol for the Western Australian Illicit Substance Evaluation (WISE) study, a research project investigating illicit drug use in the ED. Methods: Patients can be enrolled if the treating clinician strongly suspects they are currently intoxicated with a stimulant, hallucinogenic or cannabinoid drug; and an i.v. cannula or blood tests are required for routine clinical care. Patients are enrolled under a waiver of consent. A single additional blood tube is collected, de‐identified and frozen on site. A temporary link between patient identification number and study identification number is retained for up to 10 business days post‐hospital discharge to allow for clinical data collection, before this is destroyed and the patients become permanently de‐identified. Samples are transported for external liquid chromatography‐mass spectrometry analysis in batches once de‐identified. Results: The key outcome will be identification of any psychoactive drugs present in the blood sample, together with their respective concentration. This will be linked to the clinical effects, as well as being compared with the substance the patient believed they had taken. Conclusion: We consider the novel approach outlined forms a template for an early warning system for emerging drugs of concern, while also providing vital and comprehensive information on current drugs of abuse, their clinical effects and their impact on the health system.